FOUCAULT IN TELETUBBYLAND: REREADING TELETUBBIES - S. M., Niyas (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper examines Teletubbies on the basis of Michel Foucault’s theoretical framework, exploring how the show entrenches his concepts of power, control, and subjectivity. Far from being a simple children's programme, Teletubbies illustrates the pervasive nature of power as it shapes behaviours and identities within a controlled environment. Elements such as the Voice Trumpets, which disseminate commands and knowledge, and the omnipresent Noo-Noo, silently enforcing order, serve as metaphors for Foucauldian mechanisms of discipline and surveillance. By analysing these components, the paper foregrounds how Teletubbies falls in line with Foucault's theories on power’s subtle operation and its role in creating docile subjects. This rereading repositions the show within broader cultural and philosophical discourses on power, knowledge, and control.